Optimal planning of AC-DC hybrid transmission and distributed energy resource system: Review and prospects - Liu, Xianglong; Liu, Youbo (CSEE Journal of Power and Energy Systems, 2019)
With the highly-extensive integration of distributed renewable energy resources (DER) into the grid, the power distribution system has changed greatly in the structure, function and operating characteristics. On this ground, An AC-DC hybrid DER system becomes necessary for effective management and control over DER. This paper first summarizes the physical characteristics and morphological evolution of AC-DC hybrid DER system. The impact of these new features on system configuration planning is analyzed with respect to its flexible networking, rich operation control modes, and tight source-network-load-storage coupling. Then, based on a review of the existing research, problems and technical difficulties are figured out in terms of converter modeling, steady-state analysis, power flow calculation, operating scenarios management, and optimization model solution. In light of the problems and difficulties, a framework for the configuration optimization of AC-DC hybrid DER systems is proposed. At last, the paper provides a prospect of key technologies from six aspects including morphology forecasting, coupling interaction analysis, uncertainty modeling, operation simulation, optimization model solving algorithm and comprehensive scheme evaluation.